Pemanfaatan Media Interaktif dalam Pembelajaran Geografi pada Masa Pandemi - Ika Pujiastuti; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
In the 21st century, technological developments are increasingly advanced and very rapid. The role of interactive multimedia is increasingly playing a role in the field of education in line with the growth of computer users and the growth of the internet in society which increasingly facilitates the flow of multimedia products, both in the form of videos, animations, Google applications for assessment and for learning both online and offline. Along with the Covid-19 pandemic, it is increasingly visible the importance of the role of technology to be able to harmonize learning that runs remotely (online). The ability to make learning interactive, pro-student designing appropriate media adapted to the conditions of different students. Integrating multimedia and then pouring it into a storyboard is a key to the success of an interactive multimedia product development project. Learning geography during the Covid-19 pandemic requires new methods and media so that geography learning remains fun, interactive and able to increase student interest in learning geography, through interactive multimedia learning geography is expected to improve the quality of learning.